2012
DOI: 10.1111/j.1463-6409.2012.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating molecular support for and against the monophyly of the Peritrichia and phylogenetic relationships within the Mobilida (Ciliophora, Oligohymenophorea)

Abstract: Evaluating molecular support for and against the monophyly of the Peritrichia and phylogenetic relationships within the Mobilida (Ciliophora, Oligohymenophorea). -Zoologica Scripta, 42, 213-226. An ongoing debate in ciliate molecular phylogenetic analyses is whether the Peritrichiacomposed of the Sessilida and the Mobilida -are monophyletic. To further investigate this group, here we increase taxon sampling with four further mobilids: Trichodinella sp., Trichodina pectenis, Urceolaria serpularum and Urceolaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…On one hand, its secondary structure is consistent with the Urceolariidae within the Helix 12 and Helix 37, and on the other hand, it resembles the Trichodinidae within other regions. From another aspect, T. hypsilepis clustered in one separate clade within the phylogenic tree here and the analogous trees ever reported before [21].Therefore, the research results above indicated that T. hypsilepis probably evolved independently within family Trichodinidae. Nevertheless, the data of secondary structure seemed to be detrimental to ascertain taxonomic status of T. hypsilepis in the genus Trichodina, because another important reason is that no data about the morphological material for T. hypsilepis available which could conform to its molecular sequence up date; besides, in the phylogenic tree, it diverged before all the other species of genus Trichodina but after the Urceolaria.…”
Section: The Relationship Between the Secondary Structure And Topologsupporting
confidence: 69%
See 2 more Smart Citations
“…On one hand, its secondary structure is consistent with the Urceolariidae within the Helix 12 and Helix 37, and on the other hand, it resembles the Trichodinidae within other regions. From another aspect, T. hypsilepis clustered in one separate clade within the phylogenic tree here and the analogous trees ever reported before [21].Therefore, the research results above indicated that T. hypsilepis probably evolved independently within family Trichodinidae. Nevertheless, the data of secondary structure seemed to be detrimental to ascertain taxonomic status of T. hypsilepis in the genus Trichodina, because another important reason is that no data about the morphological material for T. hypsilepis available which could conform to its molecular sequence up date; besides, in the phylogenic tree, it diverged before all the other species of genus Trichodina but after the Urceolaria.…”
Section: The Relationship Between the Secondary Structure And Topologsupporting
confidence: 69%
“…Meanwhile, if no identification errors happened on T. hypsilepis, the genus Trichodina should be the more ancestral group compared with genus Trichodinella. Combined with the other biological character, Urceolariidae species have more primitive adhesive disk with very undeveloped denticles in morphology, and they are always found to parasitize on invertebrates rather than vertebrates, which is distinctly different from Trichodinidae ones parasitic on fishes and amphibians except those invertebrates [21]. Therefore, the secondary structure of V6 has proved the family Urceolariidae primitive status with the additional evidence.…”
Section: The Structural Evolutionary Trend Within the Mobilida Based mentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, Zhan et al (2009) proposed that the mobilids be separated from the sessilids and established as the new subclass Mobilia. Zhan et al (2013) increased the sample size of mobilids and successfully recovered peritrichs as monophyletic; however this relationship had no statistical support.…”
Section: Introductionmentioning
confidence: 99%
“…Partial SSUrDNA nucleotide sequences of nine Trichodina species and two Trichodinella species (family Trichodinidae) were obtained from the Genbank database under the following accession numbers: T. ; T. pectenis (JQ663868: Zhan et al, 2013); and T. sinipercae (EF599288). A multiple sequence alignment analysis was performed, and a phylogenetic tree was constructed using the neighbor-joining method and ClustalW ver.…”
Section: Ssurdna Phylogenetic Tree Analysismentioning
confidence: 99%